Development of corrosion risk map for Peninsular Malaysia using climatic and air pollution data - Fathoni U. (Institute of Physics Publishing, 2023)
Malaysia has catapulted to an era of major transition. This rapid transition has also cause impact to the environment. The human activities contribute to pollutions. Buildings and it component's performances are affected directly or indirectly by air pollutions and climate factors. It has triggering and accelerating degradation processes. When deterioration start, service life of the buildings and its components will decrease. This paper presents initial development of corrosion risk map for Peninsular Malaysia using Geographical Information System (GIS). The air pollution and climate data obtained from Malaysia Meteorology Department (MMD). The air pollution data was the salt ion deposition of nitrate, chloride and sulphate in a form of wet fall out (WFO). The corrosion risk map generated using geographical information system (GIS) using inverse distance weighing (IDW) and weighted overlay method. It found that the corrosion risk map can be generated with further site verification and it can be used by engineers for further prediction of service life of building components in achieving sustainable construction design. Published under licence by IOP Publishing Ltd.